Terpenoids from marine soft coral of the genus Xenia in 1977 to 2019 - Ng, Shean-Yeaw; Phan, Chin-Soon; Takahiro Ishii; Takashi Kamada; Toshiyuki Hamada; Charles Santhanaraju Vairappan (Molecular Diversity Preservation International, 2020)
Members of the marine soft coral genus Xenia are rich in a diversity of diterpenes. A total of 199 terpenes consisting of 14 sesquiterpenes, 180 diterpenes, and 5 steroids have been reported to date. Xenicane diterpenes were reported to be the most common chemical skeleton biosynthesized by members of this genus. Most of the literature reported the chemical diversity of Xenia collected from the coral reefs in the South China Sea and the coastal waters of Taiwan. Although there was a brief review on the terpenoids of Xenia in 2015, the present review is a comprehensive overview of the structural diversity of secondary metabolites isolated from soft coral genus Xenia and their potent biological activity as reported between 1977 to 2019.